EFFECTS OF HUMAN RESOURCE INFORMATION SYSTEM ON PERFORMANCE OF COMMERCIAL BANKS IN KENYA: A CASE OF KENYA COMMERCIAL BANK - OPIYO, PERES ADHIAMBO; Abok, Dr. Alice (IJRDO - Journal of Business Management, 2015)
In today’s knowledge-economy, organizational success depends tremendously on the performance of human resource management (HRM). Furthermore, Human Resource Management (HRM) has recently turned its concentration of knowledge sharing and strategic workforce analysis and has been increasingly evolving into a significant contributor on the organizational strategic management. The study sought to assess the Effects of Human Resource Information System on Performance of Commercial Banks; a case of Kenya Commercial Bank. More specifically, it aimed at examining how recruitment, training, payroll administration and succession planning affect performance of commercial banks and more specifically in Kenya Commercial Bank. The study adopted a descriptive survey design. The target population of the study was all the 369 staffs of Kenya Commercial bank. The researcher used stratified random sampling method to select the desired sample size of 148 respondents (40%) from the project Managers, HR executives and few staffs. Data collected was cleaned, pretested, validated, and coded, summarized and analyzed using statistical package of SPSS V21. The study findings were presented using graphs, histograms, bar charts and pie charts. Conclusions were derived based on the P.value and the coefficient of determination. ERecruitment, E-Training, E-Payroll administration and E-Succession planning was found positive and significantly related to performance. HRIS is one of the most important strategic areas for the development of banks interaction with internal and external clients besides product improvement and competition with other banks. It can be more than a tool for following the employees’ basic demographic data and working hours. It can be a tool for identifying highly potential employees and directing them to areas of their working interest thereby enhancing performance.